The capybara conspiracy : a novel in three acts - Perl, Erica S. (Alfred A. Knopf Books for Young Readers, 2016)
Fed up with their sports-obsessed school, seventh-grade playwright Olive and her best friend Reynaldo decide to kidnap the school's capybara mascot in an attempt to get more benefits and respect for non-athletes.